The Caucasian branch of the Russian Technical Society as the center of the technical thought of the southern Caucasus region - S. V. Hurinchuk (History of science and technology, 2014)
The article analyzes and summarizes the role of the Russian Technical Society’s Caucasus department in spreading technical thought in the late XIX - early XX century in the Caucasus. Relying on experience and achievements of national science and technology author has grounds to assert that rapid development of domestic industries and national economy in the period of capitalist development in the Russian Empire led to the scientific information accumulation and the necessity of its concentration around certain centers. Under such conditions the creation of the technical periodicals of the Russian Technical Society’s Caucasus department was dictated by the needs of the Caucasus region, which acutely needed a quick and competent solution of technological problems in upbringing scientific and technical personnel.